Verrucous epidermal nevus as a manifestation of a type 2 mosaic PTEN mutation in Cowden syndrome. Issue 1 (24th September 2022) - Plana‐Pla, Adrià; Condal, Laura; Jaka, Ane; Blanco, Ignacio; Castellanos, Elisabeth; Bielsa, Isabel
Abstract: Linear Cowden nevus, also known as linear PTEN nevus, is a type of epidermal nevus, first described in 2007, which is seen in patients with PTEN hamartoma tumor syndrome. It is considered to be a type 2 form of segmental mosaicism, and we suggest that it has certain clinical features that distinguish it from epidermal nevi seen in similar conditions, such as Proteus syndrome. We present a case of linear Cowden nevus in a 4‐year‐old boy and review the literature.